The blue pearl of Asia : flooding as an urban asset : a beautiful and resilient future Phnom Penh - Englund, Gunilla; Ryttar, Sara (SLU/Dept. of Urban and Rural Development, 2008)
Surface water drainage is together with water supply and wastewater management key parts of infrastructure in urban areas. As landscape architects we aim to find solutions that envisage aesthetical, social and ecological perspectives as well as technical. These aspects often go hand in hand and together they are part of the sustainability concept.